A study on gaseous extinguishing agent sensing with a simple measurement method. (13th February 2018) - Guan, Yu; Lu, Song; Yuan, Wei; Qian, Hanjie
Abstract: As research on the concentration distribution for evaluating the effectiveness of a gas fire extinguisher system is quite important, the proper sensing technology is necessary. Here, a simple method used for measuring the concentration of agent is introduced, and the manufacture of the sensing part is described clearly. The sensing unit is composed of a pressure reducing structure and pressure sensor element. The detection was achieved by sensing the change of pressure difference caused by gas flow. In order to verify the theory and characterize the sensing performance, two types of fire extinguishing agents, bromotrifluoromethane (CBrF3 ) and heptafluoropropane (C3 HF7 ), were used in the experiments. The results showed a high sensitivity from 0 to 100%, good repeatability and fast response/recovery time. Furthermore, the effect of operating temperature, humidity and geometric structure on the response were investigated. Measurements showed, for CBrF3, that the temperature had a linear impact on the response and the influence of humidity in the sensor was negligible. Through the analysis of the geometry parameter, it was found that the sensing performance could be greatly improved through adjusting the geometry structure. This technique provides a low-cost and highly reliable sensor for the detection of gaseous extinguishing agent that can be easily fabricated.